Taxation to the consumption of motion pictures and consumer attendance to cinema by Peruvian films - Cornejo Vilcarino, José Luis (2021)
Objective: Determine the relationship between consumption taxation of motion pictures and consumer attendance to the cinema for Peruvian films in the period 2017-2019. Method: The investigation was quantitative, correlational, cross-sectional and descriptive. The design was non-experimental. The sample was comprised of 384 consumers between the ages of 15 to 53 years old who attended Cineplanet’s Civic Center of Lima location during the period of 2017-2019. Results: There is a low inverse significant correlation, with a coefficient of r = -0,238, between consumption taxation of motion pictures and consumer attendance to the cinema for Peruvian films, because even if the scenario of no consumption taxation for national motion pictures is posed, 5,73% of the respondents indicate that consumer attendance would be low; 17,71%, regular; 47,14% high; and 5,73%, very high, while for 23,69% there is no correlation between the variables. Conclusion: Even without perfect inverse correlation of variables, the consumption taxation of motion pictures is one of the components that influence the consumer's decision whether go to the movies for Peruvian films or not.